Sub-Saharan Africa Refinery Study - Hammitt, James (World Bank, Washington, DC, 2014)
Over the past two decades, the growing awareness of the role that emissions play in human health and environmental degradation had led to a general movement in many parts of the world to control emissions to reduce the impacts. This movement has mainly taken two forms: 1) the development and subsequent required use of control devices for stationary sources and vehicle sources and, 2) changes in the specifications of transportation fuels to reduce emissions of the major pollutants. These trends originated in the industrialized countries and are now spreading, at different rates, throughout the world. As in other world regions, the first improvement in the specifications of transportation fuels in Sub-Saharan Africa was the elimination of lead. The phase out of lead is now complete and the World Bank and its partners are looking at the next step the reduction of sulfur in transportation fuels. The growing complexity of the vehicle emission control technologies for both personal vehicles and commercial trucks and the concomitant need for clean fuels.In addition to the growing awareness of the human health and environmental impact of vehicle source emissions, have placed increasing requirements on refineries. Sulfur is not an additive but a natural part of crude oil. Its removal processes presents both technological and economic challenges to refiners. However, by coming later than Organization for Economic Co-operation and Development (OECD) regions to ultra-low sulfur fuels, SSA refineries are in a position to benefit from the operating experience and process improvements obtained elsewhere in the refining industry.